Financial Strategies to Increase the Profitability of Women-Owned MSMEs: Focus on Liquidity, Solvency, Asset Turnover, and Business Capital from a Behavioral Perspective - Wahid, Dimas Lanang Rizky; Tubastuvi, Naelati; Purwidianti, Wida; Utami, Restu Frida (Jurnal Ilmiah Global Education, 2025)
Currently, MSMEs are mostly managed by women. The purpose of this study is to analyze the financial performance of women in MSMEs in Purwokerto. This study uses primary data. Data collection was carried out by distributing questionnaires to female MSME owners in Purwokerto. The method applied as a sampling technique was the Convenience sampling method with a sample size of 150 respondents. Then, the respondent data was processed using SmartPLS software. The steps carried out in data processing were outer model testing, model feasibility testing, and hypothesis testing. The results of the study indicate that Liquidity, assets, and business capital have a positive and significant effect on the profitability of women's MSMEs. Solvency does not affect the profitability of women's MSMEs. The variables of liquidity, assets, and business capital have been shown to play a very important role in improving financial performance and stopping the business of women's MSMEs in Purwokerto.